Pembaruan Sistem Pembayaran Zakat dalam Pasal Undang-Undang No. 23 Tahun 2011 tentang Pengelola Zakat - Firdaus, Wihda Yanuar; Hermanto, Agus (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2022)
In practice, when the concept of tax is implemented, there is often a lack of transparency in its distribution. In contrast, zakat has clear rules that must be fulfilled by the muzakki (payer) and distributed to eight eligible categories of recipients. This raises the question of whether an individual should pay both taxes and zakat or choose to pay only one. Based on the identified issues, the research formulates the following problems: 1) What is the Islamic legal perspective on the implementation of zakat collection systems in Law No. 23 of 2011 on Zakat Management? 2) What is the perspective of maslahah (public benefit) regarding the zakat collection system in Law No. 23 of 2011 on Zakat Management? This study aims to: 1) Understand, logically and scientifically, the implementation of zakat collection under Law No. 23 of 2011 in the perspective of Islamic jurisprudence (fiqh); and 2) Gain deeper insights into the maslahah values of Law No. 23 of 2011 and propose a legal zakat collection system, along with deterrent measures for those who fail to pay zakat. This is a qualitative research study in the form of a literature review, employing a philosophical-juridical approach to analyze the regulations, particularly Law No. 23 of 2011, with a focus on aligning zakat collection with tax systems that ensure public benefit. The findings suggest that the influence of Shariah economic law on zakat management can provide substantial insight, which could inform considerations for improving the understanding of Islamic principles in Indonesia. Comprehensive ijtihad (juridical reasoning) indicates that the effort to raise awareness and encourage zakat payment should be properly managed by the government, with penalties or fines imposed on those who fail to fulfill this religious obligation, as it is an essential duty in Islam